SELECTION OF RAILWAY BALLAST BASED ON CEMENTING POTENTIAL: A CASE STUDY IN THAILAND (GEOMATE Journal, 2023)
The properties of fresh ballasts collected from five quarries around Thailand were investigated in the laboratory.  The investigation includes properties specified by the State Railway of Thailand (SRT) for ballast, i.e., rock type, sieve analysis, flat and elongation, and Los Angeles abrasion.  Furthermore, cementing value, water absorption, specific gravity, sulfate soundness, and petrographic analysis were also conducted.  The obtained rock properties were then compared with the requirements for use as a ballast specified by various national standards, including the Australian Rail Track Corporation (ARTC), the American Railway Engineering and Maintenance of Way Association (AREMA), and the State Railway of Thailand (SRT).  The results show that all rocks generally comply with all standards.  However, Buriram basalt is considered the best.  Saraburi limestone has low abrasion resistance and high cementing value due to its carbonate nature which tends to give higher cementing strength.  Igneous and metamorphic rocks usually have plagioclase as their parent mineral which gives low cementing potential.  A large abundance of plagioclase in igneous rock, such as Buriram basalt, Nakhon Sawan dacite, and Prachinburi andesite, results in lower cementing values.  Rock with high cementing value may hinder its usage as a railway ballast; therefore, the cementation property of ballast by cementing value test, initially suggested by Raymond [1], is strongly recommended as additional criterion in the selection of a ballast.